Verifying earplug attenuation and evaluating the effectiveness of one‐on‐one training along with earplug fit testing at nine facilities in China. Issue 9 (11th July 2021) - Gong, Wei; Zhang, Jingjing; Liu, Xin; Ding, Enmin; Zhu, Baoli
Abstract: Background: The purpose of this study was twofold: (1) to measure the personal attenuation ratings (PARs) in Chinese workers wearing hearing protection devices (HPDs), to evaluate the effectiveness of the single number rating (SNR), the noise reduction rating (NRR), and the associated derated values of earplugs; and (2) to evaluate the effectiveness of one‐on‐one training along with earplug fit testing on PAR improvement. Methods: Noise exposure measurements, one‐on‐one training, and fit tests to measure earplug attenuation were conducted at nine manufacturing facilities located in eastern China from 2016 to 2017. 503 workers participated in the study. Ninety‐three percent were male. 199 workers were provided one‐on‐one training. Results: Before training, 14% and 15% of the workers achieved the attenuation predicted by the manufacturer's SNR and NRR, 56% and 65% exceeded the derated SNR and NRR, respectively. Following one‐on‐one training, mean PAR improved significantly by 15 dB ( p  < 0.01); 26% of the workers achieved SNR and NRR, 79% and 91% met the associated derated values, respectively. Conclusions: Labeled noise attenuation ratings and their derated values overestimated the actual level of attenuation among workers wearing HPDs. One‐on‐one training along with earplug fit testing contributed to improved PARs.